Rapid determination of viral RNA sequences in mosquitoes collected in the field - Yuki Kihara (2018)
A method for rapid determination of viral RNA sequences (RDV) was applied to homogenates of Aedes aegypti collected in Thailand in an area in which dengue fever (dengue hemorrhagic fever) is endemic, using the mosquito cell line C6/36. Nucleic acid sequences of dengue virus type 4 and cell fusing agent virus were detected. This RDV method has the potential to become a standard method for detection of both known and newly emerging, unknown mosquito-borne viruses. © 2007.